Clinical Impact of Regional Citrate Anticoagulation in Continuous Renal Replacement Therapy in Critically Ill Patients. Issue 12 (December 2017) - Huguet, Maria; Rodas, Lida; Blasco, Miquel; Quintana, Luis F.; Mercadal, Jordi; Ortiz-Pérez, Jose T.; Rovira, Irene; Poch, Esteban
Background: Regional citrate anticoagulation (RCA) is being used increasingly in continuous renal replacement therapy (CRRT) as a safer alternative to heparin. However, complex metabolic control to avoid side effects have generated discrepancies about its introduction into everyday practice. We aimed to compare both anticoagulation techniques in terms of efficacy, safety and feasibility. Methods: Observational retrospective study performed in 3 specialized ICUs in patients receiving CVVHDF with RCA between January 2013 and May 2016. Heparin-treated patients matched by age, sex and disease severity treated in the preceding year were selected as historic controls. Filter lifetime, number of filters used, haemorrhagic complications and metabolic complications were recorded. Results: 54 patients (27 treated with RCA and 27 with heparin) were included in the study. Filter lifetimes in the first 72 hours were 55.1 ± 21.8 hours in the RCA group compared to 38.8 ± 24.8 hours in the heparin group, (p = 0.004). In addition, the number of filters used in the first 72 hours was significantly higher in the heparin group (2.4 ± 1.3 vs. 1.5 ± 0.7; p = 0.004). There was a trend toward a lower incidence of bleeding in the RCA group, with a significantly lower red blood cell transfusion rate (p = 0.027) in the citrate group. No clinically significant metabolic disturbances were observed in the RCA group. Regarding outcomes, there were no significant differences between groups. Conclusions: These results suggest that the implementation of CVVHDF with RCA using concentrated citrate solutions prolongs filter lifetime, achieves a longer effective hemodiafiltration time and is a safe and feasible method.